Selected Abstracts of the 2nd International Workshop “Intensive Care of the Newborn”; Verona (Italy); March 9-10, 2018 - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2018)
Selected Abstracts of the 2nd International Workshop “Intensive Care of the Newborn”; Verona (Italy); March 9-10, 2018 CONGRESS PRESIDENT Paolo Biban Guest Editor: Paolo Biban ABS 1. DOES DELAYED CORD CLAMPING (DCC) AFFECT UMBILICAL CORD pH IN PRETERM INFANTS? • V.M. Samedi, L. Irvine, S. Thomas, D. Kowal, J. Rabi, A. Stritzke, N. Singhal, A. Abou Mehrem ABS 2. SNAP-PE SCORE. MORBIDITY AND MORTALITY INDEX IN NICUs • A. Konstantinidi, R. Sokou, S. Parastatidou, A. Tsantes, N. Iacovidou ABS 3. EARLY PERINATAL INTERVENTIONS IMPROVES NEONATAL OUTCOMES • A. Ansary, R. Lee, S. Kinmond ABS 4. DILATED CARDIOMYOPATHY AND VITAMIN D DEFICIENCY: CASE REPORT IN A PRETERM INFANT • A. Proto, S. Fiocchi, I. Gatelli, L. Ilardi, S. Martinelli ABS 5. SURVEY ON PERINATAL PALLIATIVE CARE ACROSS ITALY: PRELIMINARY RESULTS • M.E. Cavicchiolo, F. Rusalen, F. Benini, P. Lago ABS 6. PLASMA ERYTHROPOIETIN AND FETO-NEONATAL ASPHYXIA IN TERM AND PRETERM NEWBORNS • F. Dituri, L. Orfeo, A. Di Paolo ABS 7. A CHALLENGING CASE OF CONGENITAL INFANTILE FIBROSARCOMA • A. Ganarin, F. DeCorti, P. Dall’Igna, N. Doglioni, A. Berizzi, G. Bisogno, E. Baraldi, P.G. Gamba ABS 8. BIRTH ASPHYXIA IN LIMITED-RESOURCE SETTINGS: ASSOCIATED FACTORS AND OUTCOMES IN RURAL AFGHANISTAN • R. Baiocchi, M. Usuelli, P. Crosignani, E. Bruni, K. Picucci, M. Valenti, M. Langer, G. Strada ABS 9. NEONATAL HEMORRHAGE FOLLOWING MATERNAL LOW MOLECULAR WEIGHT HEPARIN (LMWH) ADMINISTRATION • A. Konstantinidi, R. Sokou, S. Parastatidou, G. Patsouras, E. Isaakidou, K. Lampropoulou, K. Adamopoulos, A. Tsantes, N. Iacovidou ABS 10. NEONATAL/INFANTILE PINOCYTOSIS. AN UNUSUAL CASE OF HAEMOLYTIC ANEMIA • R. Sokou, G. Patsouras, K. Lampropoulou, E. Tavoulari, K. Adamopoulos, M. Theodoraki, M. Kollia, A. Konstantinidi —> ERRATUM: Inadvertently, we introduced errors into the abstract during the editing process. To correct those errors, we are now publishing a corrected version of the entire abstract: ABS 10. NEONATAL/INFANTILE PYKNOCYTOSIS. AN UNUSUAL CASE OF HAEMOLYTIC ANEMIA • R. Sokou, G. Patsouras, K. Lampropoulou, E. Tavoulari, K. Adamopoulos, M. Theodoraki, M. Kollia, A. Konstantinidi. Correct version of ABS 10 can be read here: https://doi.org/10.7363/070132 ABS 11. THROMBOCYTOSIS IN NEONATES WITH NEONATAL ABSTINENCE SYNDROME THAT WERE HOSPITALIZED AT THE NICU OF GENERAL HOSPITAL OF NIKAIA • R. Sokou, E. Isaakidou, G. Patsouras, K. Lampropoulou, S. Parastatidou, K. Adamopoulos, M. Theodoraki, V. Mougiou, A. Konstantinidi ABS 12. REPEATED, BED-SIDE, NON-INVASIVE RESPIRATORY MECHANICS ASSESSMENT BY FORCED OSCILLATION TECHNIQUE IN SPONTANEOUSLY BREATHING PRETERM INFANTS DURING THE FIRST DAY OF LIFE • A. Lavizzari, C. Veneroni, M. Tossici, F. Beretta, V. Ottaviani, M. Colnaghi, F. Mosca, R.L. Dellacà ABS 13. NOISE EXPOSURE IN NICU AND DURING NEONATAL TRANSPORT: EFFECTS AND EFFECTIVENESS OF NOISE PROTECTION • N. Aminudin, D. Corcoran, A. Elkhuffash, J. Franta, N. McCallion ABS 14. NEONATAL EMERGENCY TRANSPORT SERVICE IN VENETO: NEONATAL TRANSPORT INDEX (NTI) AS A QUALITY INDICATOR • I. Sibona, M. Ventola, R. Beghini, B. Ficial, E. Bonafiglia, C.A. Forcellini, F. Bissolo, L. Chini, L. Pecoraro, S. Lauriola, A. Bertolini, M. Castellani, V. Chini, P. Biban ABS 15. INDUCTION OF NEONATAL ANESTHESIA WITH ROOM AIR VS 80% OXYGEN; AVOIDING A DECREASE IN LUNG COMPLIANCE • V. Karlsson, B. Sporre, J. Ågren, F. Fredén ABS 16. USE OF INHALED NITRIC OXIDE IN VERY LOW BIRTH WEIGHT INFANTS WITH PROLONGED PPROM • I. Sibona, B. Ficial, E. Bonafiglia, C.A. Forcellini, M. Ventola, F. Bissolo, L. Chini, L. Pecoraro, M. Castellani, A. Bertolini, S. Lauriola, R. Beghini, P. Biban ABS 17. CONGENITAL SYPHILIS: THE IMPORTANCE OF AN EARLY DIAGNOSIS • G. Morandi, F.P. Fusco, I. Lombardo, G. Vellani, S. Boccacci, E. Agazzani, M. Zanzucchi, V. Fasolato ABS 18. CHALLENGES IN VANCOMYCIN TREATMENT OF NEONATAL SEPSIS CAUSED BY STAPHYLOCOCCUS EPIDERMIDIS • A. Radsel, M. Pokorn, T. Plankar Srovin ABS 19. A QUALITY IMPROVEMENT PROJECT AIMED AT REDUCING THE INCIDENCE OF LATE ONSET INFECTIONS IN A LEVEL III NEONATAL UNIT • C. Russo, E. Bonafiglia, B. Ficial, E. Ceriani, S. Dalla Valentina, F. Manno, R. Beghini, A. Pietrobelli, P. Biban ABS 20. UNUSUAL CRP TREND IN LATE ONSET SEPSIS OF THE PREMATURE < 27 WEEKS OF GESTATIONAL AGE • S. Becciani, A. Cecchi, I. Corsini, C. Dani ABS 21. IS HAPTOGLOBIN (Hp) DOSAGE PREDICTIVE OF INFECTION IN THE FIRST WEEK OF LIFE? • F. Dituri, L. Orfeo, A. Di Paolo ABS 22. EXCESSIVE WEIGHT LOSS IN THE EXCLUSIVELY BREASTFED NEONATE DURING THE FIRST DAYS OF LIFE: A PILOT STUDY IN A GREEK MATERNITY HOSPITAL • C. Emmanouil, T. Boutsikou, I. Theochari, E. Isaakidou, A. Kontogeorgou, P. Volaki, I. Zarkada, M. Kollia, N. Iacovidou ABS 23. PERCEPTIONS OF HEALTH CARE PROFESSIONALS ON BREASTFEEDING PRACTICES • A. Kontogeorgou, N. Iacovidou, M. Kollia, V. Mougiou, S. Karamichalou, R. Sokou, E. Kokkou, P. Volaki, T. Boutsikou, Z. Iliodromiti ABS 24. POSTNATAL HYPOTROPHY IN NEWBORNS WITH EXTREMELY LOW BIRTH WEIGHT • V. Atanasova, E. Valerieva, L. Veskov ABS 25. NECROTIZING ENTEROCOLITIS AND PREMATURITY • F. Dituri, L. Orfeo, A. Di Paolo ABS 26. GROWTH AND FEEDING RATES IN THE FIRST YEAR OF LIFE IN OUR POPULATION OF LATE PRETERM AND SGA NEWBORNS: PRELIMINARY DATA • M.C. Villa, E. Portinaro, D. Ganora, F. Porcelli ABS 27. IRON PIDOLATE IN PRETERM NEWBORNS FOR PREVENTION OF ANEMIA OF PREMATURITY: FIRST METABOLOMICS RESULTS • R. Pintus, F. Cesare Marincola, S. Corbu, E. Coni, A. Dessì, M. Puddu, V. Fanos